The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil - Lucena, Daercio A. A.; Kimsey, Lynn S.; Almeida, Eduardo A. B. (Zootaxa, 2016)
The species of the chrysidid genus Ipsiura are reviewed with emphasis on the taxa occurring in Brazil. In the present study 34 Ipsiura species are recognized, diagnosed, and illustrated. Two new species are described here: Ipsiura bohartiana Lucena sp. nov. and I. duckeana Lucena sp. nov., and two others are transferred from Neochrysis to Ipsiura: I. assecia (Linsenmaier, 1997), comb. nov. and I. guayanensis (Linsenmaier, 1997), comb. nov., increasing to 41 the total of valid species in the genus. New diagnoses and redescriptions are provided for 34 species based on study of their types. For the first time, a comparative and illustrated study of male genitalia is presented for the majority of Ipsiura species. Notes on types and depository collections, a revised key for identification of species along with illustrations of diagnostic features, as well as geographical distribution maps are also given.